2013
DOI: 10.1111/hepr.12128
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of organic anion‐transporting polypeptides 1B3 and multidrug‐resistant proteins 2 increases the enhancement effect of gadolinium‐ethoxybenzyl‐diethylenetriamine pentaacetic acid on hepatocellular carcinoma in magnetic resonance imaging

Abstract: We found that coexpression of OATP1B3 and MRP2 influenced the high contrast enhancement of HCC on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Tsuboyama et al reported that increased MRP2 expression in the pseudoglands of HCCs, under the existence of OATP8, was associated with HBP hyperintense HCCs [93]. Similarly, Kimura et al reported that HCCs with high expression levels of both OATP8 and MRP2 showed a higher relative enhancement ratio of HCC on HBP images than those with lower expression levels [19]. In addition, the expression of MRP3 in HCCs has been reported to be lower in hypointense HCCs than in isoor hyperintense HCCs [23].…”
Section: Signal Intensity On the Hepatobiliary Phase: A Potential Imamentioning
confidence: 98%
See 1 more Smart Citation
“…Tsuboyama et al reported that increased MRP2 expression in the pseudoglands of HCCs, under the existence of OATP8, was associated with HBP hyperintense HCCs [93]. Similarly, Kimura et al reported that HCCs with high expression levels of both OATP8 and MRP2 showed a higher relative enhancement ratio of HCC on HBP images than those with lower expression levels [19]. In addition, the expression of MRP3 in HCCs has been reported to be lower in hypointense HCCs than in isoor hyperintense HCCs [23].…”
Section: Signal Intensity On the Hepatobiliary Phase: A Potential Imamentioning
confidence: 98%
“…Indeed, there is cumulative evidence of the value of Gd-EOB-MRI for the detection of small HCCs [14], and for the differentiation between HCCs and other hepatic lesions or hypervascular pseudolesions [15][16][17]. Furthermore, there is an emerging issue regarding the value of HBP imaging of Gd-EOB-MRI for the evaluation of multistep hepatocarcinogenesis and for predicting the prognosis of HCCs after surgery or radiofrequency ablation [18][19][20][21][22][23]. Multistep hepatocarcinogenesis can be characterized by its hemodynamic changes.…”
Section: Introductionmentioning
confidence: 99%
“…This includes organic anion transport factor 8 and organic transporter TP[11,15-17]. The enhancement also depends on the expression of multidrug resistance protein 2[16,17]. The use of Gd-EOB-DTPA to assess liver function has been reported following portal vein embolization[18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, MRP3 expression is usually weak in comparison to that of cholangiocytes [30]. In HCCs, MRP3 expression is either similar [24,30], increased [31], or decreased [19] in comparison to surrounding tissues. In tumour cells, MRP3 is localised in sinusoidal membranes [19,24,30,31] but positive staining in cytoplasm can be observed [19].…”
Section: Expression Of Mrp2 Mrp3 and Mrp4mentioning
confidence: 99%
“…In HCCs, MRP3 expression is either similar [24,30], increased [31], or decreased [19] in comparison to surrounding tissues. In tumour cells, MRP3 is localised in sinusoidal membranes [19,24,30,31] but positive staining in cytoplasm can be observed [19]. Kitao et al [23] reported that MRP3 expression was higher in isointense or hyperintense HCC than in hypointense HCC, raising the hypothesis than EOB-DTPA might return from tumour cells into sinusoids.…”
Section: Expression Of Mrp2 Mrp3 and Mrp4mentioning
confidence: 99%